THE EFFECT OF PROLANIS SERVICE INFORMATION AND TIMELINESS ON THE UTILIZATION OF PROLANIS AT JATIROGO PUBLIC HEALTH CENTER TUBAN DISTRICT - Silviana Rahmawati, Eva; Suharsoyo, Didik; Munir, Miftahul; Sudrajad, Muhammad (jfpublisher, 2022)
Introduction. The Chronic Disease Management Program (Prolanis) was a promotive and preventive program developed by BPJS Health in collaboration with Primary Health Care (FKTP). The target ratio of prolanis patient visits (RPPB) to FKTP in a safe zone was at least 50% every month. The average range of RPPB at Public Health Center Jatirogo, Tuban Regency) from January to July of 2021 was 15% out of 62 registered participants, still below the target of the safety zone determined by BPJS of Health. This study aims to analyze the effect of enabling factors and need factors on the utilization of Prolanis at the Jatirogo Health Center, Tuban Regency. Methods. This type of research is analytic research, with a cross-sectional design. The sampling technique using proportional random sampling obtained a sample of 71 employees. Results & Analysis. The result of this study showed that there was a significant influence between prolanis information (p=0.020) and time conformity (p=0.008) on the utilization of prolanis in Public Health Center Jatirogo, Tuban Regency. Meanwhile, BPJS class, distance, travel time, availability of transportation, type of transportation, social relations, health workers, health facilities, waiting time, and need have no significant effect. Discussion. The utilization of Prolanis in Public Health Center Jatirogo, Tuban Regency is influenced by prolanis information and time conformity of the patients. at Public Health Center Jatirogo, Tuban Regency needs to recollect the information of their patients, redesign the socialization media and conduct a home visit as well as discuss the schedule of prolanis activities with the patients.